ECOLOGY AND PRODUCTION IN TWO SANDY BEACHES OF GOA (PART A) DISTRIBUTION OF BACTERIA IN COLVA AND SIRIDAON IN RELATION TO CERTAIN ENVIRON MENTAL PARAMETERS - GORE, P S; SINGBAL, S Y.S (Fishery Technology, 2016)
Qualitative . and quantitative studies on the bacterial flora oftwo beaches viz , Colva and Siridaon at high tide, mid-tide andlow tide levels during the pre-monsoon period were made. Estimationsof important nutrients, like inorganic phosphates and nitratesand organic carbon have been made and correlation with thebacterial counts is being attempted. Definite correlation betweenbacterial population and organic carbon is seen; however, no correlationis observed b;;tween bacterial counts and other physicochemicalparameters.